Innovative Learning Strategies for Enhancing Student Engagement in Multicultural Classrooms - Prapai Chaanpraserta; Jennifere L. Thomas; Sarah Mitchelle; Rafael Silvat; Nandia Nkosi (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2024)
This Study For explore implementation of learning strategies innovative in class multiculturalism in Thailand and its impact to involvement student as well as challenges faced​ in manage diversity culture. Focus main study This is For analyze effectiveness use learning based on project (PBL) and technology in increase understanding students, as well as how teachers manage difference language and values culture in the classroom. Methods research used​ is approach qualitative with technique observation and interview deep towards teachers and students in several school multicultural in Thailand. Research results show that The implementation of PBL provides chance for student For collaborate in heterogeneous groups, increasing​ understanding they to different cultures and strengthen​ skills social them. Use technology learning, such as videos and online discussion platforms, have also been shown to effective in overcome constraint language and improve accessibility material for students. Although Thus, the challenge main issues faced is difference language and values culture that can influence interactions in the classroom. Teachers need to develop skills in adapt method inclusive and sensitive teaching​ to difference said. Research This recommend the need development teacher skills in management class multicultural For create a mutual atmosphere appreciate. Research more carry on required For explore impact term long from implementation of this strategy in increase quality education in schools multicultural.